The ideals of student youth in relation to the present, possible and anti-ideal - I. A. Nikolaeva (Образование и наука)
Introduction. The study of youth ideals is of traditional interest because they provide an understanding of youth values and social orientations, which determine the choice of future and current social behaviour. Ideals are a component of a single image of the world; they are interrelated with the actual (present), possible/impossible and anti-ideal as fundamental modes of human existence. The correlation of ideals with these categories reveals their functionality as regulators of social behaviour. The theories of self-concepts and identity most fully use this system of categories. However, there is still no research of these categories as a single functioning system when studying the image of the social world of young people.Aim. The aim of the current research is to study the ideals of student youth in the context of the desired/present, possible/impossible, and permissible/unacceptable (anti-ideal).Methodology and research methods. The object of research is images of “other people” with socio-group and characteristic features, freely reproduced by students. The online study involved 284 second-year students; they reproduced 6472 images of “others” and attributed 13961 features. To identify the implicit structure of the desired categories, the respondents evaluated “others” on an ungraded scale of “Bottom” (anti-ideal) – Self – “Top” (ideal). The implicit structure includes ideals; images of the present (equivalent Self); images of the desired-possible; images of the undesirable, but possible and permissible; images of the unacceptable (anti-ideals). The author compared the ideals with other evaluative and normative categories by three parameters: 1) the frequency of actualisation in consciousness (relevance); 2) socio-group (institutional) specificity; 3) the value-added content of characteristic features.Results. The frequency of updating images was determined: ideals (7.9%), present (15.4%), desirable-possible (21.9%), undesirable, but possible and permissible (44.9%), anti-ideals (5.6%). Frequency reflects the relevance of categories in the general evaluation and regulatory system, and the probability of their occurrence in students’ minds in a situation of uncertainty. The socio-institutional specificity of ideals lies in the predominance of older and female images, images of relatives, parents and representatives of science. The priority of “loved ones” combines ideals-standards with the composition of the present, and orientation to “distant ones” as anti-ideals. It was found that the content of the ideals represents the hierarchy of personal students’ values and includes several levels: 1) central values are communicative and altruistic; they have the same frequency in all the compared categories; 2) the first level of significance is the values of knowledge; their relevance increases in terms of the possible-desired; 3) the second level is the values of achievement, struggle and risk, practical activity, physical data and comfort; their relevance increases in the samples of the possible (desirable and undesirable); 4) the third level is the values of social normativity; their relevance increases for anti-ideals. The images of the present indicate a low relevance of struggle, risk and achievements. The images of the possible correspond to ideals in the content of values, and reflect the values of the second level most specifically and differentiated. The most relevant are the samples of the undesirable possible.Scientific novelty. The values and social attributes of ideals are considered in relation to the categories of the present, possible (desirable and undesirable), anti-ideal. Quantitative relations of these categories in the current consciousness of young people are described.Practical significance. The results are useful for analysing and predicting the social behavior of young people.